2011
DOI: 10.1159/000325224
|View full text |Cite
|
Sign up to set email alerts
|

Activating Effects of Chronic Variable Stress in Rats with Different Exploratory Activity: Association with Dopamine D1 Receptor Function in Nucleus Accumbens

Abstract: Background/Aims: Rats display persistent behavioural phenotypes of low (LE) versus high (HE) exploratory activity in the exploration box paradigm. LE rats that prefer passive coping strategies show differential dopaminergic activity in the striatum. The main hypothesis of this study was that chronic variable stress (CVS) would have a higher impact on LE rats. Methods: Animals were submitted to a CVS regimen lasting 32 days that was followed by a behavioural test battery. The functional states of their dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 186 publications
0
6
0
Order By: Relevance
“…Some specific stressors are unpredictable; however, stress itself is not, thus, an adaptive response to chronic variable stress is expected (Matrov et al . 2011). The potential role of the daily exposure to different stressors in the dynamics of body systemic regulation remains to be elucidated, as this hypothesis was beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Some specific stressors are unpredictable; however, stress itself is not, thus, an adaptive response to chronic variable stress is expected (Matrov et al . 2011). The potential role of the daily exposure to different stressors in the dynamics of body systemic regulation remains to be elucidated, as this hypothesis was beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, relationships between D1 mRNA expression and RDT performance were likely not attributable to differences in shock experience in the task. Although there is some evidence that chronic uncontrollable stress can alter D1 receptors (Rasheed et al, 2010; Matrov et al, 2011) it seems unlikely that shock experience in the RDT was experienced as stressful in the same manner, as it was easily avoidable and freely chosen (Maier et al, 2006). Additionally, no relationships were observed between shock experience and several measures of anxiety (Experiment 2), indicating that even high levels of shock experience in the RDT caused no lasting changes in stress- or anxiety-related behavior.…”
Section: Discussionmentioning
confidence: 99%
“…As DA turnover in the nucleus accumbens and striatum was found to be affected by stress and/or amphetamine, next we examined the protein levels of D1R and TH, the rate-limiting enzyme in the synthesis of DA. Indeed, previous research by our group (Matrov et al, 2011) had revealed that chronic stress could increase the D 1 receptor-mediated cyclic adenosine monophosphate (cAMP) accumulation in the nucleus accumbens in the rat. However, neither the sucrose preference, nor CVS regimen and repeated amphetamine treatment affected the expression level of the TH and D1R receptor protein levels.…”
Section: Discussionmentioning
confidence: 99%